What hinders the transition towards a bio-based construction sector? A global innovation system perspective on its value chain - Mazzoni, Francesca; Losacker, Sebastian; Justus Liebig University Giessen (My University, 2024)
The construction sector is heavily polluting and an actual threat to the natural environment, therefore its transition towards becoming bio-based is imperative. This transition is currently unfolding and it is driven in particular by innovation activities taking place along the sector’s value chain. In the upstream segment, bio-based materials are being improved, while novel building techniques in the core segment enable the use of these materials. In this paper, we utilize the global innovation systems (GIS) framework to examine these innovation activities and their valuation dynamics. In particular, we investigate how the GIS of the bio-based construction sector is organized along its value chain, providing insights into the barriers to the sector's sustainability transition. Our empirical analysis, based on a rich set of expert interviews, demonstrates that the GIS configuration changes along the value chain, driven by profound differences in the innovation mode. This situation creates a bottleneck that hinders the sector's transition, where knowledge about bio-based materials developed upstream fails to translate down the value chain. However, we also find that several niche firms cover and integrate multiple value chain segments and overcome this knowledge gap, suggesting that the transition towards a bio-based construction sector could accelerate with further innovation system reconfigurations.
Keywords: ddc:910